2016 updated Thai Rheumatism Association Recommendations for the use of biologic and targeted synthetic disease-modifying anti-rheumatic drugs in patients with rheumatoid arthritis - Worawit Louthrenoo (2018)
© 2017 Asia Pacific League of Associations for Rheumatology and John Wiley & Sons Australia, Ltd Aim: In June 2015, the Thai Rheumatism Association (TRA) approved an update of its recommendation for the use of biologic disease-modifying anti-rheumatic drugs (bDMARDs) and targeted synthetic (tsDMARD) in the treatment of rheumatoid arthritis (RA) to cover those currently available in Thailand (etanercept, infliximab, golimumab, rituximab, tocilizumab, abatacept and tofacitinib). Method: A search of the literature was performed between January 2000 and June 2015. Existing RA recommendations, in relation to the use of bDMARDs and tsDMARD, were identified and evaluated by the AGREE II instrument prior to their use as a ‘guide’ for developing this TRA recommendation. An additional literature search was performed in order to answer specific clinical questions that could not be found in existing guidelines. Result: Thirteen recommendations were developed. They covered the use of RA classification criteria, the aim of RA treatment, when to initiate bDMARDs/tsDMARD or taper or switch them to other medications, as well as monitoring these drugs during their use. In addition, specific issues including their use and vaccination, malignancies, pregnancy and lactation, and perioperative period also were addressed. Public hearings were performed at the annual meeting of the TRA and of the Royal College of Physicians of Thailand. The recommendations were distributed to other professional associations related to RA management, as well as government sectors associated with the reimbursement policy, prior to development of the final version. Conclusion: These recommendations will help Thai rheumatologists prescribe bDMARDs and tsDMARD more appropriately when treating RA patients.